A new concept of station–keeping system for deep water production units – type FPSO. (4th April 2012) - Grove, MÁ?rcio De Abreu; Portella, Ricardo; Levi, C.
An innovative concept of station–keeping system to be used in Floating, Production, Storage and Offloading (FPSO) production units located in deep waters is described. The new concept combines the conventional catenary mooring lines (namely, spread mooring), in a special configuration known as 'Differential Complacency Anchoring System – DICAS', with thrusters controlled by dynamic positioning system. The chief idea behind such a hybrid system is to design the conventional mooring system just enough to support the usually mild operational environmental loads and consider thruster assistance to cope with the more severe survival conditions. Such a combination may allow for reducing the total number and/or size of the mooring lines to be employed. In addition, the occasional use of the thrusters reduces their working time, having a positive impact on their operational costs and reliability. As one may expect, acquisition, installation and maintenance costs of the conventional mooring system are largely dependent on water depth. On the other hand, dynamic positioning costs are nearly constant with respect to water depth. Therefore, it would be possible for a given environmental condition to find the water depth above what it would become more economic to install the hybrid system in the FPSO. A further benefit obtained from the hybrid system is due to the horizontal complacency of the DICAS mooring line arrangement. The thruster lets interventions, applied to change FPSO heading, to reduce, within certain limits, the hull roll motions when energetic swells come from aside (beam seas). As a result, the FPSO working time and operational safety index may be accordingly increased.